2014
DOI: 10.3892/etm.2014.1959
|View full text |Cite
|
Sign up to set email alerts
|

Levels of CD105+ cells increase and cell proliferation decreases during S-phase arrest of amniotic fluid cells in long-term culture

Abstract: The present study aimed to improve the characterization of amniotic fluid cells (AFCs) in order to optimize their use in chromosomal prenatal diagnosis and as seed or stem cells for tissue engineering. The AFCs used in the current study were obtained from three females in their second trimester of pregnancy. The cells were cultured independently and characterized by cell morphology, cell markers, cell cycle distribution and chromosome Giemsa banding in an early- and late-passage. The AFCs remained homogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Additionally, other studies have shown the ability of AFMSCs to modulate the immune system, leading to restriction of T lymphocyte proliferation [8]. Moreover, increased CD105+ levels were found in the late-passage of the cell culture in contrast to the early-passage ASFC culture [9]. This provides evidence of AFSCs role as a mesenchymal precursor, in that the prevalence of CD105 and the longterm culture conditions permit mesenchymal cell growth [9].…”
Section: Stemness Of Cells Derived From the Amniotic Fluidmentioning
confidence: 71%
See 1 more Smart Citation
“…Additionally, other studies have shown the ability of AFMSCs to modulate the immune system, leading to restriction of T lymphocyte proliferation [8]. Moreover, increased CD105+ levels were found in the late-passage of the cell culture in contrast to the early-passage ASFC culture [9]. This provides evidence of AFSCs role as a mesenchymal precursor, in that the prevalence of CD105 and the longterm culture conditions permit mesenchymal cell growth [9].…”
Section: Stemness Of Cells Derived From the Amniotic Fluidmentioning
confidence: 71%
“…Moreover, increased CD105+ levels were found in the late-passage of the cell culture in contrast to the early-passage ASFC culture [9]. This provides evidence of AFSCs role as a mesenchymal precursor, in that the prevalence of CD105 and the longterm culture conditions permit mesenchymal cell growth [9]. A recent in vitro investigation determined the gestational age (i.e., those derived from first-, second-to thirdtrimester) that influence AFSCs' function in regulating the proliferation of lymphocytes [10].…”
Section: Stemness Of Cells Derived From the Amniotic Fluidmentioning
confidence: 98%
“…Their progeny do not conform to the positive cell marker criteria set by International Society of Cell Therapy for MSCs. Previous publications show variation in CD105 in early culture and an increase in CD105 expression with more time in culture (Anderson, Carrillo‐Gálvez, García‐Pérez, Cobo, & Martín, ; Pittenger et al, ; Wang et al, ). It is possible that the progeny of CTPs from trabecular surface cells may go on to fully express all three markers at high levels after a longer period of expansion.…”
Section: Discussionmentioning
confidence: 89%
“…Other recent studies have shown immunomodulatory properties of AFMSCs, which can inhibit the proliferation of T lymphocytes [8]. In another study, cultured AFSCs demonstrated an increase in CD105+ cells in the late-passage compared with the early-passage AFSC cultures [9]. Because CD105 is a mesenchymal marker and the long-term culture conditions allowed mesenchymal cell growth, AFSCs have been suggested to be mesenchymal precursors [9].…”
Section: Stemness Of Cells Derived From the Amniotic Fluidmentioning
confidence: 99%
“…In another study, cultured AFSCs demonstrated an increase in CD105+ cells in the late-passage compared with the early-passage AFSC cultures [9]. Because CD105 is a mesenchymal marker and the long-term culture conditions allowed mesenchymal cell growth, AFSCs have been suggested to be mesenchymal precursors [9]. Recent in vitro analysis has found that AFSCs modulate lymphocyte proliferation in different manners according to gestational age (i.e., those derived from first-, second- or third-trimester) [10].…”
Section: Stemness Of Cells Derived From the Amniotic Fluidmentioning
confidence: 99%